AGRARIAN MOVEMENT AND AGRICULTURAL LABOURERS OF PUNJAB:CHALLENGES AND WAY FORWARD - Kumar, Vijay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The depiction of migrant labourers in transit has reignited discourse surrounding our adopted economic model and the substantive security afforded to our labour class. The imposition of COVID-19 lockdowns further imperilled agricultural labourers, shedding light on their predicaments—previously marginalized within mainstream deliberations. While contentious farm laws and labour codes dominated discussions, the plight of agricultural labourers remained eclipsed by the predominant focus on farmers and urban labourers. Our contention lies in the unprecedented participation of labourers in the farmers’ protests, rallying under the unifying slogan "Kisan Mazdoor Ekta Zindabad" (Long Live Farmer-Labourer Unity). Nonetheless, this solidarity predominantly stemmed from a broader spectrum of support for the farming community, rather than from a specific focus on the challenges faced by agricultural labourers. This article endeavours to explicate the potential ramifications of the recently repealed triad of farm laws on agricultural labourers, elucidating their present vulnerabilities. Moreover, it seeks to unravel the underlying reasons behind the relatively subdued participation of these labourers in protests and the marginalization of their issues within the recent farmers’ movement. Finally, it offers recommendations aimed at ameliorating the circumstances of agricultural labourers.